Acetone Sensing Properties of a Gas Sensor Composed of Carbon Nanotubes Doped With Iron Oxide Nanopowder - Qiulin Tan; Jiahua Fang; Wenyi Liu; Jijun Xiong; Wendong Zhang (Sensors, 2015)
Iron oxide (Fe2O3) nanopowder was prepared by a precipitation method and then mixed with different proportions of carbon nanotubes. The composite materials were characterized by X-ray powder diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. A fabricated heater-type gas sensor was compared with a pure Fe2O3 gas sensor under the influence of acetone. The effects of the amount of doping, the sintering temperature, and the operating temperature on the response of the sensor and the response recovery time were analyzed. Experiments show that doping of carbon nanotubes with iron oxide effectively improves the response of the resulting gas sensors to acetone gas. It also reduces the operating temperature and shortens the response recovery time of the sensor. The response of the sensor in an acetone gas concentration of 80 ppm was enhanced, with good repeatability.